Research Progress in Multielectron Reactions in Polyanionic Materials for Sodium‐Ion Batteries. Issue 4 (25th October 2018) - Liu, Rui; Liang, Ziteng; Gong, Zhengliang; Yang, Yong
Abstract: Realizing multielectron reactions in electrodes is crucial for improving the capacity and energy density of batteries. Polyanion‐type compounds are suitable for exploring multielectron reactions due to their robust frameworks and structural diversity. This paper reviews the recent research progress on the study of multielectron reactions in Na‐based polyanion compounds. The versatile polyanions are classified by transition metals (V, Mn, Fe, Ti, Cr, and Co). Both experimental efforts and theoretical calculations are analyzed and summarized, with a special focus on the reversibility, stability, and corresponding structural evolutions during the multielectron reactions. The challenges and opportunities of exploring polyanions with reversible and stable multielectron reactions are also discussed. Abstract : Exploring multielectron reactions in cathode materials is a promising strategy to substantially improve the capacity and energy density of sodium‐ion batteries simultaneously. The newest research progress, mainly focusing on multielectron reactions of polyanionic materials, is systemically reviewed in this paper. The opportunities and critical issues in this field are also proposed and discussed for further investigations.